Strength training: In search of optimal strategies to maximize neuromuscular performance - Duchateau, J.; Stragier, S.; Baudry, S.; Carpentier, A. (Exercise and Sport Sciences Reviews, 2020)
Training with low-load exercise performed under blood flow restriction can augment muscle hypertrophy and maximal strength to a similar extent as the classical high-load strength training method. However, the blood flow restriction method elicits only minor neural adaptations. In an attempt to maximize training-related gains, we propose using other protocols that combine high voluntary activation, mechanical tension, and metabolic stress. Mechanical tension and metabolic stress contribute to training-related muscle hypertrophy and increase in maximal strength. As the magnitude of the neural adaptations after low-load exercise with blood flow restriction is less than that elicited by high-load strength training and this method is difficult for some individuals and insufficient for well-trained athletes, we suggest there is a need for new strength training protocols. One training option is to combine different levels of mechanical tension and metabolic stress that are optimized to the training status of the individual.